Principales habilidades blandas en cargos gerenciales para potencializar la cultura organizacional en las empresas constructoras MiPymes de Colombia (2023)
This research seeks to establish a guide of practical guidelines that encourage in management positions the development of the main soft skills, in the organizational culture, in order to generate competitive advantages in MSME construction companies in Colombia.